Accreditation Compulsion or Inducement : A Perception Study of Various Stakeholders - Bagga, Teena (Prabandhan: Indian Journal of Management, 2017)
This century has seen tremendous changes in higher-education institutions across the globe. The Indian education system too is witnessing a change in terms of privatization of education. Till the 1980s, the government was heavily funding these institutions because the focus then was to support the increasing demand of higher education. However, the mushrooming of private HEIs in India led the Govt. to stop the financial aid beyond the 1980s. A new National Policy on Education was drafted in 1986, and accordingly, many acts of the Parliament were passed in the following years to enforce quality assurance in higher education. Among the measures identified to ensure assurance of higher educational quality, accreditation was one. However, even after years of its existence through national accreditation agencies like NBA and NAAC since 1994, a majority of the HEIs still continue to exist and operate without an accreditation, along with a general understanding that there is a low level of awareness or understanding among the various stakeholders of higher education about the concept of ’accreditation’. The current research thus focused on ascertaining the actual figures and insights about the awareness of accreditation as well as the various perceptions which these different stakeholders held about accreditation.